2010
DOI: 10.1007/s10490-010-9220-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple agency perspective, family control, and private information abuse in an emerging economy

Abstract: Multiple agency perspective, Family control, Private information risk, Emerging economy, Hong Kong, D82, G14, G34,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 92 publications
(97 reference statements)
2
54
0
1
Order By: Relevance
“…From a principalagent perspective, PIs are acting as an agent for all actors within the entrepreneurial ecosystem, what leads to multiple agency roles. This circumstance requires the consideration of multiple governance roles of the PI in the entrepreneurial ecosystem and consequently the existence of different sets of agency costs (Filatotchev et al 2011). PIs are agents in response of the overall project, assigned and contracted to balance interests and competing claims within the ecosystem.…”
Section: Multiple-principal Agent Relationships and The Costs And Benmentioning
confidence: 99%
“…From a principalagent perspective, PIs are acting as an agent for all actors within the entrepreneurial ecosystem, what leads to multiple agency roles. This circumstance requires the consideration of multiple governance roles of the PI in the entrepreneurial ecosystem and consequently the existence of different sets of agency costs (Filatotchev et al 2011). PIs are agents in response of the overall project, assigned and contracted to balance interests and competing claims within the ecosystem.…”
Section: Multiple-principal Agent Relationships and The Costs And Benmentioning
confidence: 99%
“…Using agency theory arguments, the vast majority of research investigating the relationship between board independence and information disclosure has suggested that a higher proportion of independent directors will lead to higher levels of voluntary disclosure (Filatotchev, Zhang, & Piesse, 2011). Independent directors provide the compulsory checks of corporate financial and operational information and may thus have greater incentives than inside directors to encourage companies to disclose more information to outside stakeholders (Fama & Jensen, 1983).…”
Section: Board Independencementioning
confidence: 99%
“…On the other hand, some scholars have found hardly any differences between FBs and NFBs [7,39], have even confirmed that NFBs performed better than family owned firms. Whereas [61,62], suggest that family management has a positive effect on profitability, other authors such as Barth [58,[63][64][65][66] found that firms with family members who serve as managers underperform firms that are managed by outside managers.…”
Section: Literature Reviewmentioning
confidence: 99%